2014
DOI: 10.7860/jcdr/2014/7476.4310
|View full text |Cite
|
Sign up to set email alerts
|

Medical Thoracoscopy vs Closed Pleural Biopsy in Pleural Effusions: A Randomized Controlled Study

Abstract: Background: Pleural effusion is a common diagnostic dilemma for the pulmonologist. A histological diagnosis would many a time steer the way to an accurate diagnosis of the aetiologies of pleural effusions. This study has compared two methods for obtaining histological specimens in cases of undiagnosed pleural effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 12 publications
2
33
0
2
Order By: Relevance
“…Subcutaneous emphysema, localized infection of the incision site, hypotension, fever, atrial fibrillation during the procedure are minor; empyema, hemorrhage, tumor seeding in port site, bronchopleural fistula, pneumonia, prolonged air-leak and re-expansion pulmonary edema are the major complications reported from various studies (11). The complication rates in our study were similar to the literature; the post-operative hospitalization period was shorter in our study (Table 3) (4,8,(12)(13)(14)(15). The most common complication was subcutaneous emphysema; however, these patients had similar hospitalization days compared to the rest of the patients.…”
Section: Discussionsupporting
confidence: 85%
“…Subcutaneous emphysema, localized infection of the incision site, hypotension, fever, atrial fibrillation during the procedure are minor; empyema, hemorrhage, tumor seeding in port site, bronchopleural fistula, pneumonia, prolonged air-leak and re-expansion pulmonary edema are the major complications reported from various studies (11). The complication rates in our study were similar to the literature; the post-operative hospitalization period was shorter in our study (Table 3) (4,8,(12)(13)(14)(15). The most common complication was subcutaneous emphysema; however, these patients had similar hospitalization days compared to the rest of the patients.…”
Section: Discussionsupporting
confidence: 85%
“…The diagnostic sensitivity in previous thoracoscopic studies varied from 66% to 100%. 13,23,24 The sensitivity of thoracoscopic pleural biopsy for malignancy in present study was 92.8% and for TB was 100%. This result is comparable with the study by Sakuraba et al who studied 138 patients and reported a diagnostic efficacy of 92.6% in the cases of carcinoma, and in tuberculosis it was 93.8%.…”
Section: Figure 1: Distribution Of Agementioning
confidence: 47%
“…The non-occurrence of major complications may be because of less number (<5) of biopsies. 13,15 The sensitivity obtained for FOB was 3 out of 21 cases (14.2%) but the specificity was 100%. Very few studies were available for bronchoscopy in pleural effusion cases.…”
Section: Figure 1: Distribution Of Agementioning
confidence: 93%
“…4 Moreover, in a recent randomized controlled trial comparing the efficacy of closed pleural biopsy and MT in the diagnosis of exudative pleural effusion of unknown etiology, MT had a diagnostic yield of 86% and complication rate of 10% compared to closed pleural biopsy (62% and 17%, respectively). 19 Thus, despite repeated pleural fluid sampling and closed pleural biopsy, the etiology of pleural effusion remains unknown in up to 25% to 40% of patients. 20,21 In a systematic review evaluating the diagnostic accuracy of MT for patients with pleural effusion of undetermined etiology, MT (semirigid) had a pooled sensitivity and specificity of 97% and 100%, respectively.…”
Section: Clinical Applications Exudative Pleural Effusion Of Unknown mentioning
confidence: 99%
“…The diagnostic yield of MT is around 95% in patients with MPE and has a success rate of 90% in achieving pleurodesis. 19 Medical thoracoscopy is considered a less invasive procedure compared to VATS, requires moderate sedation, requires a single port of entry, and can be done in the endoscopy suite. Although rigid MT can obtain a larger specimen, the diagnostic yield of rigid and flex-rigid is similar in malignant pleural disease.…”
Section: Malignant Pleural Effusionmentioning
confidence: 99%